Removal of lead(II) ion in water by adsorbents from Pithecellobium dulce - Chairgulprasert, Vanida; Madlah, Nuchtima; Pohmueyae, Rukaiyah; Madmanang, Nurheedayah (KKU Science Journal, 2016)
The removal of lead(II) ion in water by the adsorbents from the fruit peels and leaves of Pithecellobium dulce has been studied using a batch method. Four parameters, contact time, pH, initial lead concentration and adsorbent dose were optimised to maximise adsorption. The maximum adsorption efficiency for the fruit peels was 90%, compared with 87% for the leaves. In both cases, the adsorption data followed second-order kinetics and fit the Freundlich isotherm. For the peels, the data were more effectively modelled using a simple Langmuir isotherm.